Analisis Tingkat Bunga, Inflasi, Likuiditas, Nilai Tukar, dan Finansial Yang Mempengaruhi Terhadap Keuntungan Saham di Bursa Efek Indonesia - Hantono Hantono; Luther Girsang (Asian Journal of Innovation and Entrepreneurship, 2016)
Shares optimal gain is the main purpose of an investor in making an investment in a company's stock . To achieve these objectives , of course, an investor should be to act selectively in assessing various potential companies , one of which is the interest rate , inflation , liquidity , exchange rate , and financial . The first aim of this study was to determine and analyze whether the interest rate will affect the profits of shares in the Indonesian Stock Exchange , both to study and analyze whether inflation will affect the profits of shares in the Indonesian Stock Exchange in the period 2010-2012 , the third to study and analyze liquidity affect profit shares in the Indonesian Stock Exchange in the period 2010-2012 , the fourth to identify and analyze the exchange rate will affect the profits of shares in the Indonesian Stock Exchange in the period 2010-2012 , the fifth to megetahui and financial analyzes will affect profit shares in the Indonesian Stock Exchange in the period 2010-2012 , and the sixth to know and to analyze whether the inflation , liquidity , exchange rate and financial will affect profit shares in the Indonesian Stock Exchange in the period 2010-2012.  Results of this study that the interest rate , inflation , liquidity , exchange rate , and financial influence together to gain share in the Indonesia Stock Exchange , while individually the interest rate effect on profit shares